Determination of peroxide value in thermally oxidized crude palm oil by near infrared spectroscopy - Moh, M. H.; Che Man, Y. B.; van de Voort, F. R.; Abdullah, W. J. W. (Wiley, 1999)
near infrared (NIR) spectroscopic method wasdeveloped to measure peroxide value (PV) in crude palm oil(CPO). Calibration standards were prepared by oxidizing CPOin a fermentor at 90°C. A partial least squares (PLS) calibrationmodel for predicting PV was developed based on the NIR spec-tral region from 1350 to 1480 nm with reference to single-pointbaseline at 1514 nm. The optimization of calibration factorswas guided by the predicted residual error sum of squares test.The standard error of calibration obtained was 0.156 over theanalytical range of 2.17–10.28 PV and the correlation coeffi-cient (R 2 ) was 0.994. The method was validated with an inde-pendent set of samples which was prepared in the same man-ner on a different day. A linear relationship between the Ameri-can Oil Chemists’ Society and the NIR methods was obtainedwith R 2 of 0.996 and standard error of performance of 0.17.This study has demonstrated that the prediction of PV in the NIRregion is possible. The method developed is rapid, with totalanalysis time less than 2 min, is environmentally friendly, andits accuracy is generally good for quality control of CPO.Paper no. J8748 in JAOCS 76, 19–23 (January 1999)